Fatal intoxication after oral ingestion of amphetamine: Two case reports - Evelyn Pawlik; Felix Mayer; Oliver Temme (Forensic Science International: Synergy)
Amphetamine is a stimulant that is abused worldwide and e.g. leads to hyperthermia [Brinkman et al., 2014], dizziness, insomnia, stomachaches and suppression of appetite [Callaway et al., 1994]. The most common production route of racemic (R-/S)-amphetamine is the Leuckart synthesis [United Nations Office on Drugs and Crime 2006, Hauser et al., 2018], where by-products like 4-methyl-5-phenylpyrimidine (4-M-5-PP), N,N-di (β-phenylisopropyl)amine (DPIA) and N-formylamphetamine (NFA) are incurred. We describe two cases in which 39 years old men died after oral intake of greater amounts of liquid amphetamine preparations. Body fluids (heart blood, femoral vein blood, urine, cerebrospinal fluid, vitreous humour, and stomach content), organ tissues (myocardium, lung, liver, gall bladder, brain and kidney) and skeletal muscle were examined for amphetamine and amphetamine by-products as well as for other substances e.g. alcohol and pharmaceuticals. Analysis were done via HPLC/DAD, LC/MS, GC/MS or GC/FID without or after fluid-fluid extraction. Amphetamine was detected in all biological materials, the highest concentrations were found in urine (2600 μg/ml, case 1) and stomach content (14,000 μg/g, case 2). The amphetamine by-product DPIA was found only in heart blood (case 2), while NFA and 4-M-5-PP could not be detected at all. Morphological findings and the toxicological results for (R-/S)- amphetamine, the amphetamine by-products, alcohol, other drugs and pharmaceuticals are shown for both cases. The amphetamine concentrations of both cases are compared and the distribution in the body is discussed. The toxicity of the amphetamine by-products on the human body remains unclear and is subject of further studies.